2002
DOI: 10.1124/dmd.30.1.1
|View full text |Cite
|
Sign up to set email alerts
|

Desacetyl-Diltiazem Displays Severalfold Higher Affinity to CYP2D6 Compared with CYP3A4

Abstract: This paper is available online at http://dmd.aspetjournals.org ABSTRACT:It has earlier been shown that the isoenzymes CYP2D6 and CYP3A4 are involved in O-and N-demethylation of diltiazem (DTZ), respectively. Apparently, CYP3A4 plays a more prominent role than CYP2D6 in the overall metabolism of DTZ. However, previous observations indicate that the opposite might be true for the pharmacologically active metabolite desacetyl-DTZ (M1). Thus, the aim of the present in vitro investigation was to study the relative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 12 publications
1
19
0
Order By: Relevance
“…It was reported that diltiazem is metabolized by CYP3A4 both in the liver and small intestine [40,41] . The absorption of diltiazem in the intestinal mucosa was inhibited by P-glycoprotein efflux pump [42,43] .…”
Section: Future Prospectsmentioning
confidence: 99%
“…It was reported that diltiazem is metabolized by CYP3A4 both in the liver and small intestine [40,41] . The absorption of diltiazem in the intestinal mucosa was inhibited by P-glycoprotein efflux pump [42,43] .…”
Section: Future Prospectsmentioning
confidence: 99%
“…Diltiazem and desmethyldiltiazem were shown to be CYP3A4 inhibitors using the approach, as expected (albeit baseline chromatographic resolution was not attainable for these two compounds). Importantly, desacetyldiltiazem was identified as a CYP2D6 inhibitor using this approach, which was reported previously (Molden et al, 2002). If this approach were used prospectively, it would have directed a closer examination of desacetyldiltiazem as a possible CYP2D6 inhibitor.…”
Section: Discussionmentioning
confidence: 74%
“…This offers an example of a metabolite possessing P450 inhibition activity although the parent drug does not. Desacetyldiltiazem was previously reported to inhibit CYP2D6 and a small dmd.aspetjournals.org DDI has been reported for diltiazem and metoprolol, a CYP2D6 substrate (Tateishi et al, 1989;Molden et al, 2002). No inhibition peaks were observed in activity-grams for the other enzymes (data not shown).…”
Section: Resultsmentioning
confidence: 80%
“…The phosphorodiamidate morpholino oligomer chemistries have been reported in the literature elsewhere [12,13,14,15,16,17,18,19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37,38,39,40,41,42,43,44,45,46,47,48,49,50,51,52,53,54,55]. A PMO, etiplersen, is currently under evaluation in clinical trials for the treatment of Duchenne Muscular Dystrophy [29,30].…”
Section: Resultsmentioning
confidence: 99%
“…Most importantly, compared to conventional antisense approaches, PMOs are highly resistant to degradation [14]. PMO compounds have demonstrated reliable and effective inhibition of gene expression including c-myc [15,16,17,18,19,20], cytochrome P4503A [21,22], and viruses including vesiviruses [23,24] and Ebola virus [25]. The PMO duplex with RNA is not a substrate for RNAseH [26] and as such they can be used to induce exon skipping in genes including dystrophin [27,28] for the treatment of patients with Duchenne Muscular Dystrophy [29,30].…”
Section: Introductionmentioning
confidence: 99%